1987
DOI: 10.1193/1.1585416
|View full text |Cite
|
Sign up to set email alerts
|

Damage-Limiting Aseismic Design of Buildings

Abstract: A procedure for earthquake-resistant design is developed to limit the potential damage of buildings to a tolerable level. The procedure is based on the damage model developed earlier (Park and Ang, 1984) in which structural damage is expressed as a function of the maximum deformation and dissipated hysteretic energy. The tolerable degree of damage is defined on the basis of calibration with observed damages from past major earthquakes. The design method is examined in the context of reliability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
182
0
17

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 416 publications
(199 citation statements)
references
References 0 publications
0
182
0
17
Order By: Relevance
“…Therefore, for each column the score may vary between 0 and 4. Based on the results of the work carried out by Park et al [8], where DIs' boundaries for each damage degree observed after earthquake events were adapted to the observed damage states as reported in previous sections, Table 4 includes proposals of DI ranges for each damage state. The DI was computed for each biaxial test using expressions (7) to (13), whilst expressions (2) and (3) were adopted to estimate the parameter β and the ultimate displacement (for each RC column direction).…”
Section: Analysis Of the Obtained Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, for each column the score may vary between 0 and 4. Based on the results of the work carried out by Park et al [8], where DIs' boundaries for each damage degree observed after earthquake events were adapted to the observed damage states as reported in previous sections, Table 4 includes proposals of DI ranges for each damage state. The DI was computed for each biaxial test using expressions (7) to (13), whilst expressions (2) and (3) were adopted to estimate the parameter β and the ultimate displacement (for each RC column direction).…”
Section: Analysis Of the Obtained Resultsmentioning
confidence: 99%
“…Concerning the ultimate deformation capacity, some expressions have been proposed based on experimental tests performed up to failure on beams and columns. Park et al [8] suggested expression (3) to estimate the ultimate displacement. According to the study performed by Fardis et al [19], it was concluded that this equation leads to the best agreement of the Park & Ang index with several experimental results analyzed.…”
Section: Original Park and Ang Damage Indexmentioning
confidence: 99%
See 2 more Smart Citations
“…Park et al (1987) proposed a story damage index D story as: where D i is the local damage index at location i and E i is the corresponding energy absorbed at location i. The energy dissipated, however, is also incorporated in the damage computation.…”
Section: Combined Damage Indexmentioning
confidence: 99%